BUILDING USE RIGHTS OVER LAND MANAGEMENT RIGHTS IN SHOPPING CENTERS - Sidiq, Azhar (Communale Journal, 2023)
This article discusses arranging building use rights (HGB) over management rights (HPL). Management rights are rights to control land that the state directly controls. Which authorizes the right holders to plan the designation and use of the land in question, use the land to carry out their duties, hand over parts of the land to third parties with use rights for 6 (six) years, and receive annual income and or obligatory money. This research uses an empirical juridical method with the Wiltop Trade Center (WTC) Mall case approach that occurred in the Jambi Province area. In the discussion, it was found that the WTC management adhered to Article 2 of the Minister of Agrarian Regulation No. 9 of 1965 concerning the Implementation of the Conversion of Tenure Rights over State Land and Provisions Concerning Policy Further.Â  It stipulates the conversion of tenure rights over State land into Management Rights, namely "If State land is given to Departments, Directorates, and Autonomous Regions, other than used for the agencies' interests.Â  Also intended to be granted with a right to a third party, the right to control the State land is converted into a Management Right. Therefore, the WTC is a third party that uses Management Rights as the basis for Building Use Rights in conducting its business. Building Use Rights are used to construct buildings, including in the form of residential or residential houses, shop houses (shops), office houses (office houses), shops, hotels, offices, and industries (factories).